Whither the evolution of the contemporary social fabric? New technologies and old socio-economic trends - Giovanni Dosi; Maria Enrica Virgillito (Global Labor Organization (GLO), 2019)
The reflections which follow build on two interrelated questions, namely, first, whether we are witnessing another “industrial revolution”, and second, what is the impact of technological transformations upon the current dynamics of the socio-economic fabric, especially with respect to employment, income distribution, working conditions and labour relations. We argue that the processes of innovation and diffusion of what we could call “intelligent automation” are likely to change, or more likely reinforce, the patterns of distribution of income and power, which have been there well before the arrival of the technologies we are concerned about: some are indeed intrinsic features of capitalism since its inception, while others are features of the last thirtyforty years. First, we shall offer a fresco of such tendencies which certainly preceded any potential “Fourth Industrial Revolution” but are going to be amplified by the latter. Second, we discuss the features of such possible new techno-economic paradigms. Third, we examine the relationships between technology, productivity and growth, and the ensuing impact on jobs, division of labour, distribution of knowledge, power, and control. Finally, we address some policy implications.
Keywords: O10; E6; D63; F6; 330; Social fabric; technology; macroeconomic development; division of labour; knowledge; inequality